2022
DOI: 10.3390/ma15176169
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics and Microstructure Analysis of Alkali-Activated Slag–Fly Ash Cementitious Material

Abstract: Modifying the admixture of alkali-activated cementitious materials using components such as fly ash and fine sand may reduce CO2 emissions and conserve natural resources and energy. This study adopted strength testing, scanning electron microscopy, and mercury intrusion porosimetry to investigate the influence of different admixtures on the compressive strength and flexural strength of alkali slag cementing materials and the microstructure characteristics of hardened slurry under the action of load. The flexur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This study investigates the drying and autogenous shrinkage values of alkali-activated slag (AAS) cementitious materials with varying fly ash and fine sand contents. With the author's previous research results on the strength development law of alkali slag cementing materials, it can be found that the addition of these materials can improve the shrinkage performance of AAS at the expense of some mechanical strength [22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study investigates the drying and autogenous shrinkage values of alkali-activated slag (AAS) cementitious materials with varying fly ash and fine sand contents. With the author's previous research results on the strength development law of alkali slag cementing materials, it can be found that the addition of these materials can improve the shrinkage performance of AAS at the expense of some mechanical strength [22].…”
Section: Discussionmentioning
confidence: 96%
“…To mitigate this issue, the author proposes replacing slag powder with fly ash or fine sand to reduce the shrinkage value. Previous studies have investigated the effects of adding fly ash and fine sand on the physical and mechanical properties of alkali-activated slag cementitious materials [22]. The results showed that when the amount of fly ash does not exceed 50% or the amount of fine sand does not exceed 20%, the effect on the strength of the cementitious material is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Further enhancement of grouting material performance can be achieved by optimizing the addition amounts, combinational types, and process parameters of ISWs. Zhu et al [84] prepared cementitious materials using slag and fly ash as raw materials under alkali activation. The findings revealed that the compressive strength initially increased and then decreased with a decreasing fly ash content when 3% sodium hydroxide (by mass) was used as an alkali activator and the water-to-solid ratio was 0.4.…”
Section: Industrial Solid Waste Incorporation and Process Optimizationmentioning
confidence: 99%
“…Therefore, it is crucial to focus on reducing, capturing, storing, and utilizing CO 2 in the cement and concrete industry. The most common research in this field involves CO 2 reduction, which includes reducing carbon emissions during cement production and finding alternatives to cement [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%